Research during COVID-19 Pandemic: Perspectives from the Ethics Committees of a Lower Middle Income Country - Ghimire, N.; Panthee, A.; Sharma, M. R.; Adhikari, R. K.; Gyanwali, P. (Kathmandu University Medical Journal, 2020)
The pandemic of Coronavirus Disease 2019 (COVID-19) has created paradoxically a good opportunity globally to conduct research in the field of health and social science, and a Lower Middle-Income Country (LMIC) like Nepal is not an exception in this regard. During this ongoing pandemic, the Ethical Review Board (ERB) of Nepal Health Research Council (NHRC) has received numerous research proposals regarding COVID-19. As its main responsibility is to ensure participants’ safety, at the same time maintaining the scientific standard of research, the ERB has meticulously gone through all the proposals received so far. During this situation of a health emergency, the ERB of NHRC has had a different experience compared to the usual time. Its strength, weakness, opportunities, and threats have been like never before.